Revealing the relationship between acceptance and understanding of evolution through NOS (Nature of Science)-based learning - Shefa Dwijayanti Ramadani; Ika Sukmawati (Universitas Ahmad Dahlan, 2022)
Evolution is considered the central and unifying theme of the discipline of Biology. Yet, some debates refusing the theory of evolution raise and lead to a problem in understanding the evolution process. This study aimed to examine the relationship between acceptance and understanding of the concept of evolution in pre-service biology teachers with solid religious and educational backgrounds. A correlational design was employed in this current study. The study subjects were students of the Biology Education Department of Universitas Islam Madura, which has implemented NOS (Nature of Science)-based learning. All subjects are Muslims, and 86.84% pursued their education in Islamic boarding schools. The data was measured using MATE (Measure of Acceptance of the Theory of Evolution) and ECK (Evolution Content Knowledge). The study’s findings indicate a significant relationship between acceptance and understanding of the concept of evolution. In addition, the acceptance of the concept of evolution contributed 63.6% towards the understanding. These findings suggest that acceptance of evolution is essential to understand it and that teaching evolution by implementing NOS-based learning is a necessary step to improve students’ acceptance and understanding of the concept of evolution.